Pengaruh Minat Belajar Dan Perhatian Orang TuaTerhadap Prestasi Belajar Siswa Kelas TinggiSD Negeri 01 Wonolopo Tahun Ajaran 2014/2015 - DARMAWAN, Ricky; , Drs. Muhroji, S. E., M.Si., M.Pd (2015)
he purpose of this study (1) To determine whether there is influence student interest on student achievement Elementary School high grade Wonolopo 01. (2) To determine whether there is parental influence on student achievement high grade SDN 01 Wonolopo. (3) To determine whether there is influence students' interest and attention of parents on student achievement high grade SDN 01 Wonolopo .. This research is descriptive quantitative research with a conclusion through analysis stasistik. The entire study population of students of high grade (IV, V, VI) SDN 01 Wonolopo totaling 87 students. The study sample consisted of 12 students kels IV, 12 fifth grade students and 12 sixth grade students of SD Negeri 01 Wonolopo. The sampling technique using a stratified random sampling. The technique of collecting data using questionnaires and documentation. Data were analyzed using multiple linear regression analysis, t test, F test, the coefficient of determination, SR and SE are preceded by analysis prerequisite test is a test of normality and linearity test. Based on the analysis of multiple linear regression equation: Y = 40,127+ 0,266X1 + 0,220X2. Results of the data analysis significance level of 5% was obtained: (1) Interest in learning affects the learning achievement. This is based on test results t is known that t count> t table, namely 0.266> 2.032 and the significance value <0.05 is 0.032 with the relative contribution of 48.2% and the effective contribution of 12.7%. (2) Attention parents influence on learning achievement. This is based on test results t is known that t count> t table, namely 2.328> 2.032 and the significance value <0.05, namely 0.026 with the relative contribution amounted at 51.6% and the effective contribution of 13.5%. (3) Interest in learning and Perhatia parental influence on learning achievement. This is based on test F known that Fhitung> Ftable is 5,858> 3.28 and a significance value <0.05, namely 0.002.